Anterior Esthetic Rehabilitation Using Socket Shield Technique with Immediate Implant Placement– A Case Report - Rathod, Asha; Mistry, Gaurang; Bachhav, Mayuri; Bhatia, Tanupriya; Mehta, Kunal; Pokharkar, Amit (Journal of Neonatal Surgery, 2025)
Anterior Tooth Replacement Poses Significant Esthetic And Functional Challenges, Particularly In Cases Requiring Extraction In The Maxillary Esthetic Zone. The Socket Shield Technique (Sst), A Form Of Partial Extraction Therapy, Offers A Biologically Driven Approach To Preserve The Buccal Root Segment And Maintain The Surrounding Bone And Soft Tissue Architecture. This Case Report Presents The Management Of A 35-Year-Old Female Patient With A Fractured Maxillary Right Lateral Incisor, Treated Using Sst With Immediate Implant Placement And Provisionalization. Atraumatic Decoronation, Careful Root Sectioning, And Shield Preparation Were Followed By Palatal Osteotomy, Implant Placement, Bone Grafting, And The Fabrication Of A Screw-Retained Provisional Crown. The Technique Preserved The Facial Contour, Prevented Soft Tissue Collapse, And Allowed For A Seamless Esthetic Transition. The Patient Demonstrated Excellent Healing With No Postoperative Complications. This Report Highlights The Clinical Relevance And Predictability Of Sst In Optimizing Esthetic Outcomes And Accelerating Rehabilitation In The Anterior Maxilla When Executed With Precision.